Pengaruh Transformasi Struktural dan Pertumbuhan Ekonomi terhadap Ketimpangan Pendapatan di Sulawesi Tenggara (Journal of Regional and Rural Development Planning (Jurnal Perencanaan Pembangunan Wilayah dan Perdesaan), 2024)
Economic development basically focuses its attention on the process of changing the underdeveloped economic structure so as to enable the emergence of new industries to replace the agricultural sector as the driving force of economic growth. The industrial sector has the largest contribution to the formation of the Gross Regional Domestic Product in Southeast Sulawesi Province. However, when considering employment absorption by sector, the concentration of labor absorption remains focused on the agriculture and services sectors. The industrial sector has the smallest share in terms of employment absorption among sectors in Southeast Sulawesi Province. The aim of this research is to analyze the influence of structural transformation and economic growth on income inequality in Southeast Sulawesi Province. The method used is panel data regression analysis. Research findings show that the transformation of the industrial sector, the transformation of the industrial sector without mining, and economic growth have a negative impact on income inequality. Meanwhile, the service sector transformation variable and economic growth without the mining subsector have a positive impact on increasing income inequality in Southeast Sulawesi Province.